A Giant Left Atrial Myxoma Neovascularized from the Right Coronary Artery - Demet Menekse Gerede; Irem Muge Akbulut; Sadık Ersoz; Mustafa Kilıckap (Case Reports in Cardiology, 2015)
Myxomas are benign and the most common tumors of the cardiac muscle (Reynen, 1995). They are predominantly located in the left atrium. Clinical manifestations may vary according to the localization and the size of the myxoma. On the other hand, imaging of a myxoma by contrast dye during coronary angiography is a rare sign, which displays the vascular supply of the tumor. Here, we report the case of a 51-year-old man presenting with presyncope and palpitations due to a giant left atrial myxoma having its vascular supply from the right coronary artery (RCA).